(untitled) (Research, Society and Development, 2020)
This is a descriptive, prospective longitudinal study with a qualitative approach that had as its scenario the Undergraduate Nursing Course of a private institution in the city of Rio de Janeiro. This objective is to analyze the training path for the acquisition of teaching skills of the teaching nurse in the application of active methodologies (AM). Semi-structured interviews were conducted from September to November 2019 with seven professors of the Undergraduate Nursing Course. The institution invests in training and webinars that some teachers think are not enough to support the process. Only two participants reported having previous experience with active methodologies. It was identified that the institution did not sponsor some paid applications indicated for use in certain disciplines. It was noticed, however, that everyone dedicates themselves and invests believing in the emancipatory potential that MAs can promote in the teaching-learning process. Future analyses could draw more concrete conclusions from the investment of AM.